Developing Peer-to-Peer (P2P) Energy Trading Model for Malaysia: A Review and Proposed Implementation - Heng Y.B.; Ramachandaramurthy V.K.; Verayiah R.; Walker S.L. (Institute of Electrical and Electronics Engineers Inc., 2023)
Coal industry; Costs; Electric industry; Energy policy; Power markets; Solar power generation; Electricity-market structure; Energy trading; Malaysia; Peer to peer; Peer to peer (P2P); Renewable energies; Renewable energy source; Solar photovoltaics; Trading mechanism; Trading models; Renewable energy resources